The practice of "Solvency-II" for pension fund and non-life insurance sustainability business towards government debt - Djuminah,; Deviar, Alfiansyah (International Journal of Management and Sustainability, 2025)
This research was conducted to find out how insurance companies with business sustainability insure government-run pension funds, which are vulnerable to the risk of default. The research focuses on the 18 OECD countries in the period 2011 to 2022 with the Path Analysis approach. The data are retrieved from World Bank Data and OECD website database; furthermore, the data quality is guaranteed. Although this study is conducted at the end of 2024, the research data for 2023 was incomplete, so it did not fulfil the balanced panel requirement. Hypothesis testing results show that pension funds affect non-life premiums. Then pension funds have a significant effect on both government debt and non-life insurance undertakings. Furthermore, pension funds affect government debt through non-life premiums. Similarly, pension funds affect non-life undertakings through non-life premiums. If the loss value is too large, the insurance company, jointly with other insurance companies, will share the risk of compensation. This collection of insurance companies is called the Insurance Undertaking. With Solvency-II, we will be able to bridge between non-life insurance companies and the government in risk prevention. Therefore, non-life insurance companies everywhere should strictly implement risk mitigation guidelines in accordance with the provisions in their respective countries.